Management of Acromioclavicular Osteoarthritis in Rotator Cuff Tears: A Scoping Review - Compagnoni, Riccardo; Stoppani, Carlo; Menon, Alessandra; Cosmelli, Nicolò; Fossati, Chiara; Ranuccio, Francesco; Randelli, Pietro (Joints, 2019)
Purpose The treatment of acromioclavicular joint (ACJ) osteoarthritis during shoulder arthroscopy is a discussed topic. The aim of this scoping review is to report the current recommendations regarding the management of this disorder in patients undergoing surgery for rotator cuff tears.Methods A scoping review was performed in Pubmed\Medline and Embase in March 2017, restricted to English language literature. The following keywords were used: (“rotator cuff tear” OR ” rotator cuff” OR “rotator cuff repair”) AND (“acromioclavicular joint arthritis” OR “ac joint arthritis” OR “ac joint” OR “acromioclavicular joint”). Inclusion criteria were randomized controlled trials, prospective cohort studies, retrospective trials, and therapeutic case series. Exclusion criteria were reviews, meta-analyses, and expert opinions.Results Two retrospective studies and three randomized controlled trials were identified. Clinical studies reported results of 443 shoulders, with an average age of 60.48 years and a mean follow-up of 31.7 months. Many differences were found regarding the design of the studies, patient's selection, surgical procedures, and instrumental and clinical evaluations. No statistically significant differences were found in clinical outcome scores between patients that underwent rotator cuff repair in association with distal clavicular resection and patients with isolated rotator cuff repair.Conclusion Results of this scoping review underline a lack of evidence-based recommendations about the management of ACJ osteoarthritis in association with arthroscopic rotator cuff repair. Surgical procedures such as distal clavicle resection (DCR) should be performed carefully in this cohort of patients. More prospective randomized studies are needed to reach a consensus about the correct surgical approach to DCR in patients with signs of ACJ osteoarthritis and rotator cuff tears.Level of Evidence Level III.
Keywords: distal clavicle resection; rotator cuff repair; acromioclavicular joint osteoarthritis; shoulder